2008
DOI: 10.1097/sap.0b013e31816b31f8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Angiosarcoma of the Scalp

Abstract: Angiosarcomas (AS) of the scalp are rare tumors with an extremely poor prognosis mostly affecting elderly patients. Given the special anatomic nature of the blood supply to the scalp, it must be presumed that the tumor has already spread at the time of the initial presentation. We report a simple and fast surgical procedure, which places only a minimum burden on the patient. In 19 patients, we performed a resection of the external table with the defect being covered immediately by a split skin graft. The avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 21 publications
3
25
0
Order By: Relevance
“…In 2008, Buschmann et al 21 reported on a series of 19 patients with sHN CAS and suggested surgery should be limited to a debulking procedure that allows for permanent defect cover in order to reduce both patient morbidity and extended surgical recovery time that may delay the ability to start adjuvant therapy. Guadagnolo et al 2 also reported on the extent of surgical resection, stating standard of treatment at their institution for H/N CAS consists of neoadjuvant chemotherapy before gross resection of tumor without attempt at negative margins followed by radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, Buschmann et al 21 reported on a series of 19 patients with sHN CAS and suggested surgery should be limited to a debulking procedure that allows for permanent defect cover in order to reduce both patient morbidity and extended surgical recovery time that may delay the ability to start adjuvant therapy. Guadagnolo et al 2 also reported on the extent of surgical resection, stating standard of treatment at their institution for H/N CAS consists of neoadjuvant chemotherapy before gross resection of tumor without attempt at negative margins followed by radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excision is currently the curative treatment of choice for patients with resectable angiosarcoma of the scalp. However, even when tumors have been completely resected with wide surgical excision, local control rates are exceedingly poor at ≤25% (3,(6)(7)(8). Therefore, postoperative radiation therapy has been used to minimize local recurrence.…”
mentioning
confidence: 99%
“…This was echoed by Buschmann et al 13 who also included patients with palliative resection in outcome evaluation; their longest survival reported was 36 months. This is similar to our experience where longest survival was 42 months.…”
Section: Discussionmentioning
confidence: 74%